The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1186/1471-230x-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the recovery time of alfentanil and fentanyl in balanced propofol sedation for gastrointestinal and colonoscopy: a prospective, randomized study

Abstract: BackgroundThere is increasing interest in balanced propofol sedation (BPS) titrated to moderate sedation (conscious sedation) for endoscopic procedures. However, few controlled studies on BPS targeted to deep sedation for diagnostic endoscopy were found. Alfentanil, a rapid and short-acting synthetic analog of fentanyl, appears to offer clinically significant advantages over fentanyl during outpatient anesthesia.It is reasonable to hypothesize that low dose of alfentanil used in BPS might also result in more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
6
29
1
Order By: Relevance
“…Toklu et al [7] compared remifentanil + propofol and remifentanil + etomidate in patients who underwent colonoscopy under sedation and reported that the mean discharge times were 32.8 and 24.6 minutes, respectively. The mean discharge time in our study was approximately 15 minutes (15.1 vs 15.7 minutes) in both groups, which was similar to the studies that showed that the mean discharge times were around 15 minutes using moderate sedation for colonoscopy [8][9][10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Toklu et al [7] compared remifentanil + propofol and remifentanil + etomidate in patients who underwent colonoscopy under sedation and reported that the mean discharge times were 32.8 and 24.6 minutes, respectively. The mean discharge time in our study was approximately 15 minutes (15.1 vs 15.7 minutes) in both groups, which was similar to the studies that showed that the mean discharge times were around 15 minutes using moderate sedation for colonoscopy [8][9][10].…”
Section: Discussionsupporting
confidence: 90%
“…It is believed that pain, distension of colon, stretching of the mesentery, and sedation regimen provoke these symptoms [1][2][3][4][5][6][7][8][9][10]. In our study, no vasovagal reactions were observed in any patients.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…1992, Engelhard et al . 1999 ).This so-called "admixture" is commonly used in humans for sedation (Ho et al . 2012 ), although it is not free of complications and may cause respiratory depression (Yoon et al .…”
Section: Introductionmentioning
confidence: 99%
“…These advantages make it an attractive analgesic supplement for short ambulatory surgical procedures [13,14]. Clinically, analgesia with propofol-alfentanil combination has been widely used in short surgical procedures [15][16][17] such as arthroscopy, bunionectomy, esophagogastroduodenoscopy, lithotripsy and ureteroscopy. Fospropofol produces a predictable pharmacokinetic and pharmacodynamic profile by delivering controlled sedation in an outpatient setting.…”
mentioning
confidence: 99%